PERILAKU MAKAN LUTUNG JAWA DI HUTAN RAKYAT KABUPATEN CIANJUR - Faizi, Fuja Hikmawan; Srimulyaningsih, Reni (Fakultas Kehutanan Universitas Winaya Mukti, 2023)
Javan langur (Trachypithecus auratus) is one of endemic species of Indonesia and one of them is in community forest of Pamoyanan Village, Cianjur Regency, West Java. The object of research is to know feeding behavior of Javanese langur. The methods used by focal animal sampling combined with scan sampling methods. The results of feeding behavior of javan langur in the community forest of Pamoyanan Village had a different way for each feed species and had the highest frequency of feeding activity, are chewing 1165 times and swallowing 93 times. The preference times for eating are 06.00-08.00 WIB and 15.00-16.10 WIB. The feed species of javan langur are mahoni (Swietenia mahagoni), jati (Tectona grandis), Tisuk (Hibiscus macrophylus) and mindi (Melia azedarach), rambutan (Nephelium lappaceum) and duku (L. parasiticum).